Insight. Intermediate: teacher's book - Mare C. de la Christina (Oxford Exam Support)
The Teacher's Book includes in-depth teaching notes with additional cultural and language information for full classroom support, as well as extra activities that allow flexibility in your lessons. The Teacher's Book also includes the answer keys and audio scripts for the material found in the Student's Book. The accompanying Teacher's Resource Disk provides a wealth of additional resources to support your lesson content. This includes additional communication worksheets to practice key language from the Student's Book, documentary video clips with worksheets and lesson guides, a functional language bank of key communicative phrases and a writing bank of key writing formats used in the course. The Disk also includes suggestions for classroom activities such as teaching creative writing, involving technology-expert students and using video.